A Qualitative Study Investigating How Small and Medium Manufacturing Companies Manage Outsourcing Risk - Alshayban, Laila (2014)
Outsourcing strategies are a critical decision for many organizations. While many companies benefit from outsourcing in expanding their business, others fail to meet their objectives. The strategy is linked to serious issues such as product safety, product recall and ethical issues. Today, many firms consider bringing the outsourced activity back in-house due to these issues. Thus, the need to manage and plan for the success of the strategy is essential. The aim of this paper is to explore how managers in small- to medium-sized manufacturing organizations manage outsourcing risks. The investigation used an interview for data collection with five managers of five different manufacturing companies in the United Kingdom. The empirical study found that the risk-management process was ignored completely before making the decision to outsource, and it was not used effectively after outsourcing implementation. The SMEs relationship with suppliers did not take the form of a formal customer-supplier relationship. In fact, it was more of a regular purchasing decision because no written contract was set for a long-term or short-term relationship. In almost all of the cases, companies made only an oral commitment to continue the relationship. Moreover, operational problems observed in most of the cases were due to a lack of communication and the buyers’ unclear expectations and objectives. Despite the fact that the decision was not based on the risk analysis results, outsourcing seems successful for most small- and medium-sized manufacturing enterprises. The research findings make an important contribution to the risk-management field in supply chain concepts as it increases our knowledge about outsourcing in SMEs. It also helps SMEs develop a better understanding of how important it is to identify risks in order to avoid the problems they faced.